Gravity for Domestic and International Alliances: A CAGE Perspective - Engsig, Juliane; Chiambaretto, Paul; Le Roy, Frédéric (Management international / International Management / Gestiòn Internacional, 2018)
This paper assesses the relevance of the Gravity model to investigations of alliance flows within and between countries. Accordingly we aim to identify how different distance dimensions impact the alliance partner choice. Inspired by economics research, we use the Gravity model to estimate and analyse bilateral alliance flows within countries and between country pairs. Our results show that the richer the companies’ home countries are, the more alliances are found between firms of these two countries. We also reveal that too much geographic and cultural distance between two countries decreases the number of alliances signed between firms of these countries.